High‐throughput identification of novel heat tolerance genes via genome‐wide pooled mutant screens in the model green alga Chlamydomonas reinhardtii. (24th December 2022) - Mattoon, Erin M.; McHargue, William E.; Bailey, Catherine E.; Zhang, Ningning; Chen, Chen; Eckhardt, James; Daum, Chris G.; Zane, Matt; Pennacchio, Christa; Schmutz, Jeremy; O'Malley, Ronan C.; Cheng, Jianlin; et al.
Abstract: Different high temperatures adversely affect crop and algal yields with various responses in photosynthetic cells. The list of genes required for thermotolerance remains elusive. Additionally, it is unclear how carbon source availability affects heat responses in plants and algae. We utilized the insertional, indexed, genome‐saturating mutant library of the unicellular, eukaryotic green alga Chlamydomonas reinhardtii to perform genome‐wide, quantitative, pooled screens under moderate (35°C) or acute (40°C) high temperatures with or without organic carbon sources. We identified heat‐sensitive mutants based on quantitative growth rates and identified putative heat tolerance genes (HTGs). By triangulating HTGs with heat‐induced transcripts or proteins in wildtype cultures and MapMan functional annotations, we presented a high/medium‐confidence list of 933 Chlamydomonas genes with putative roles in heat tolerance. Triangulated HTGs include those with known thermotolerance roles and novel genes with little or no functional annotation. About 50% of these high‐confidence HTGs in Chlamydomonas have orthologs in green lineage organisms, including crop species. Arabidopsis thaliana mutants deficient in the ortholog of a high‐confidence Chlamydomonas HTG were also heat sensitive. This work expands our knowledge of heat responses in photosynthetic cells and provides engineering targets to improve thermotolerance in algae and crops. Summary Statement: We performed genome‐wide, pooled, quantitative, mutant screens in the unicellular green alga Chlamydomonas reinhardtii, combined with transcriptomics/proteomics and function annotation, and provided a list of 933 high/medium‐confidence genes with putative roles in heat tolerance in photosynthetic cells.